ANALISA KETELITIAN DAN KESESUAIAN PEMODELAN 3D DENGAN PENDEKATAN GEOMETRI DAN TEKNIK STRUCTURE FROM MOTION (SFM) PADA OBYEK BANGUNAN - Cahyono, Agung Budi; Ulinnuha, Rifqi (GEOID, 2016)
3D modeling has become an activity that required by other field, such as for research, visualization, inventory, maintenance, and mapping. Buildings are target object of 3D modeling, one of them is Laboratorium Rekayasa Forensik ITS building as public facility. Photogrammetry as an art, a science and technology focusedon image processingis one of basic of3D modeling, especially Close Range Photogrammetry. Modeling of existing objects can be formed from photos with several methods. 3D Modeling methods that have been developed are Geometry-approach and SFM techniques. Modeling result using Geometry-approach and SFM techniques will be qualified as good if the 3D model has accuracy level 3 (LoD 3). The object research tested are accuracy and suitability of model result to real object. Accuracy is tested by comparing ICP value of observation against ICP value of georeferenced model.The visual aspect is tested by view teh similarity of structure and texture result. While modeling suitability tested using some aspect, that is visually, detail geometry, processing duration, specification, cost, format, data, observation, performance, and file size. From this research generate 3D model of Laboratorium Rekayasa Forensik ITS building that qualified LoD 3, with RMSE value (Easting, Northing, Height) < 50 cm and suitable architecture to real object for both methods, Geometry-approach and SFM technique. Modeling 3D using both methods has each characteristic in detail aspet, duration aspect, specification aspect, cost aspect, data aspect, observation aspect, performance aspect, and file size aspect.